Exploring the role of pictures in tthe health promotional materials a production and quasi-experimental study on dengue prevention posters among the students of Talomo Central Elementary School - Cablayda, Kissel G.
Pictures are very helpful to aid the need for health communication especially in recalling health messages-this phenomenon is called the Picture Superiority effect. Hence, there is no known study that seeks to understand the role of pictures in health promotional materials. It is important to make a study that seeks to understand how to relay an effective health message through optimizing the communication channels such as pictures. Thus, this study was designed to figure out: (1) if PSE have different impact on health promotional materials; (2) is different types of pictures (e.g. illustrations or photographs) in a promotional material (poster) have significant difference on the recall messages; (3) how posters be designed and produced to enhance attention, comprehension and recall to health promotional materials. The study used a Pre-test, Post-test Control group Quasi Experimental Design among the 236 students of Talomo Central Elementary School. Results show that PSE have different impact on health promotional materials in terms that it provides no significant change in recalling the health information. There was no significant difference in the message recall before and after the two kinds of posters were presented. However, certain threats to validity may have influenced the results of the study. These are instrumentation, maturity, and selection.
Thesis (B.A. Communication Arts) -- University of the Philippines Mindanao
Keywords: Communication Arts -- Media Arts